Design and development of surface unmanned vehicle (SUV) system mechanism and vessel - Joannes Niegel, Mekiun (2022)
A Surface unmanned vehicle (SUV) is a vehicle that is operated without any crew on board. Operate in various ways such as remotely by using a remote control or autonomously by using autonomous navigation. Surveying using manned vehicle may cost a lot especially in terms of requirement of passenger or crew and limited for risky task that may have potential to jeopardize the passenger or crew such hazardous or confined area. A remote-operated unmanned vehicle is able to carry out the task more economically and efficiently with unmanned features. The SUV is an alternative feature for a surface vehicle such as a boat and ship in which remotely operated and some with autonomous configuration. However, the current existed commercial SUV majority with the high prices either because of the brand or the size of market that still not reach the essential product level. Therefore, this project has taken initiative to develop an optimal cost of SUV boat with a simple design using the catamaran concept. Two hulls are created from Polyvinyl Chloride (PVC) Plastic parts and the body made by polystyrene. Also, this project is designed with a wireless remote control with radio frequency (RF) transmission, has real-time viewing on surface water vehicle and Global Positioning System (GPS) unit to configure the coordinate location of the SUV with Global System for Mobile Communication/General Packet Radio Service (GSM/GPRS) technology to upload the data information in customized graphical user interface (GUI) software. The controller unit for the propulsion of the SUV is developed remotely operated and this system is also covered on driving the rudder of the vehicle for pitching its motion. The expected outcome of the project is to develop a mini-SUV prototype with long-haul wireless control and monitoring for the calm and low tidal water area.